The effects of measurement error on the MAX EWMAMS control chart. Issue 12 (18th June 2017) - Daryabari, S. Abedin; Hashemian, S. Mohammad; Keyvandarian, Ali; Maryam, Shekary A.
ABSTRACT: Recently, some researchers suggested using a single chart to monitor both location and scale parameters for a process simultaneously, in order to resolve some difficulties in control chart interpretation arising from the traditional approach. This study focuses on the Maximum Exponentially Weighted Moving Average and Mean Squared deviation (MAX EWMAMS) control chart in the presence of measurement error. An important issue in using this chart is that measurement error adversely affects the performance of the chart. In this study, we investigate the effects of measurement error on the performance of the MAX EWMAMS chart by calculating and comparing the average time to signal ( ATS ) associated with both the in-control and out-of-control states.